MANAJEMEN PENDIDIKAN AL-QUR’AN DI SIRI SORI ISLAM KEC. SAPARUA TIMUR - M Sahrawi Saimima (al-Iltizam: Jurnal Pendidikan Agama Islam, 2022)
Abstract: Management in its operational stages is an effort to encourage students to follow the directions given by the teaching staff at TPQ. Siri sori Islam around 1970 is known as the country with the most Qori' and Qori'ah producers in Maluku Province. Meanwhile, in carrying out this research, qualitative research methods were used with observational data collection techniques, interviews and documentation. The results of this study show that TPQ needs to play an active and effective role in increasing interest in reading the Qur'an, especially in tilawah and tartil by updating information about the development of MTQ such as through Youtube. Then, it is necessary to participate in the participation of the District Tilawatil Qur'an Development Institute in collaboration with TPQ in terms of bringing in Tilawah or Tartil trainers who have competence in their fields, so that in the process of coaching and networking MTQ participants at TPQ for the time being, they can get participants who are considered maximum. Keywords; Education management, Qur'anic Education